Danton - Przybyszewska, Stanisława 1901-1935; Prodromidès, Jean 1927- (Concorde Home Entertainment GmbH, 2013)
Georges Danton, the popular revolutionary leader, returns to Paris at a time when the new Republic is in disarray. Robespierre and his allies have set up a monstrous dictatorship, beginning the infamous "Reign of Terror." Danton pleads with the people for an end to the bloodshed which violates the spirit of their revolution.
Bonus: Original Kinotrailer
Original: Frankreich, Polen 1983
Bildformat 1.66:1 (16:9)
Keywords: Danton, Georges Jacques <1759-1794> -- Drama; Przybyszewska, Stanisława <1901-1935> -- Film adaptations; Robespierre, Maximilien <1758-1794> -- Drama; Geschichte; Revolutionaries -- France -- Drama; Frankreich; France -- History -- Reign of Terror, 1793-1794 -- Drama; Film; DVD-Video; Biographical films; Feature films; Fiction films; Film adaptations; Foreign films; Historical films; Motion pictures, French